Planar Lebesgue Measure of Exceptional Set in Approximation of Subharmonic Functions - Girnyk, Markiyan (Журнал математичної фізики, аналізу, геометрії, 2009)
We consider the pointwise approximation of a subharmonic function having finite order by the logarithm of the modulus of an function up to a bounded quantity. We prove an estimate from below of the planar Lebesgue measure of the exceptional Set in such approximation.Mathematics Subject Classification: 31C05, 30E10